Reconstructing Community, Recreating Boundaries. Identity Politics and Production of Social Space in Post-War Vukovar - Kardov, Kruno (Array, 2006)
The paper deals with social correlates of territorial transition with particular stress laid on the problem of disappearance of cultural codes and social norms. The influence of war crimes trials on the processes of communities' reconstruction is analysed through two elements: opposition between legal norms and moral norms of local community, and processes of nationalisation of urban space that unfolds through changes of street names, of urban architecture and symbolic representation of the city on postcards.